2012
DOI: 10.1002/pd.4002
|View full text |Cite
|
Sign up to set email alerts
|

Clinical application of massively parallel sequencing‐based prenatal noninvasive fetal trisomy test for trisomies 21 and 18 in 11 105 pregnancies with mixed risk factors

Abstract: Objective To report the performance of massively parallel sequencing (MPS) based prenatal noninvasive fetal trisomy test based on cell-free DNA sequencing from maternal plasma in a routine clinical setting in China. MethodThe MPS-based test was offered as a prenatal screening test for trisomies 21 and 18 to pregnant women in 49 medical centers over 2 years. A total of 11 263 participants were recruited and the MPS-based test was performed in 11 105 pregnancies. Fetal outcome data were obtained after the expect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
258
1
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 208 publications
(265 citation statements)
references
References 36 publications
3
258
1
2
Order By: Relevance
“…This is a screening test performed to determine fetal chromosomal status from genetic material in a maternal blood sample. Though only made available commercially in the last year or two, NIPD testing is successful in >99% of patients with high sensitivity and specificity [Papageorgiou et al, 2011;Dan et al, 2012;Nicolaides et al, 2012;Ashoor et al, 2012]. NIPD is preferred by women, according to a recent study by Hill et al [2012], and are able to detect the most frequent trisomies and XY aneuploidies.…”
Section: Methods Of Prenatal Diagnosismentioning
confidence: 99%
“…This is a screening test performed to determine fetal chromosomal status from genetic material in a maternal blood sample. Though only made available commercially in the last year or two, NIPD testing is successful in >99% of patients with high sensitivity and specificity [Papageorgiou et al, 2011;Dan et al, 2012;Nicolaides et al, 2012;Ashoor et al, 2012]. NIPD is preferred by women, according to a recent study by Hill et al [2012], and are able to detect the most frequent trisomies and XY aneuploidies.…”
Section: Methods Of Prenatal Diagnosismentioning
confidence: 99%
“…2,3 Multiple clinical validation studies using either targeted or whole-genome sequencing demonstrated the high sensitivity and specificity of NIPT. [4][5][6][7][8][9][10][11][12][13][14][15] Although most validation studies were predominantly evaluating the clinical validity in pregnancies at increased risk of the most common aneuploidies, it was recently shown that screening all pregnant women has positive predictive values of 45.5% and 40% for detection of trisomies 21 and 18, respectively. 16 MPS for aneuploidy detection applies counting statistics to millions of sequencing reads to identify subtle changes in the small percentage of fetal DNA present in the total cell-free DNA isolated from maternal plasma.…”
Section: Introductionmentioning
confidence: 99%
“…For Edwards syndrome the overall detection rate is around 97%, with a false positive rate of 0.15% and for Patau syndrome it is the lowest, 92%, with 0.2% false positive rate (18). Subsequent studies in low risk population proved that NIPT is as effective in detecting anomalies of chromosomes 21, 13, 18, X and Y (19,20).…”
Section: Single Nucleotid Polymorphism (Snp) Techniquementioning
confidence: 99%